ATRvD1 Attenuates Renal Tubulointerstitial Injury Induced by Albumin Overload in Sepsis-Surviving Mice - José Bruno N. F. Silva (MDPI AG, 2021)
Novel strategies for the prevention and treatment of sepsis-associated acute kidney injury and its long-term outcomes have been required and remain a challenge in critical care medicine. Therapeutic strategies using lipid mediators, such as aspirin-triggered resolvin D1 (ATRvD1), can contribute to the resolution of acute and chronic inflammation. In this study, we examined the potential effect of ATRvD1 on long-term kidney dysfunction after severe sepsis. Fifteen days after cecal ligation and puncture (CLP), sepsis-surviving BALB/c mice were subjected to a tubulointerstitial injury through intraperitoneal injections of bovine serum albumin (BSA) for 7 days, called the subclinical acute kidney injury (subAKI) animal model. ATRvD1 treatment was performed right before BSA injections. On day 22 after CLP, the urinary protein/creatinine ratio (UPC), histologic parameters, fibrosis, cellular infiltration, apoptosis, inflammatory markers levels, and mRNA expression were determined. ATRvD1 treatment mitigated tubulointerstitial injury by reducing proteinuria excretion, the UPC ratio, the glomerular cell number, and extracellular matrix deposition. Pro-fibrotic markers, such as transforming growth factor β (TGFβ), type 3 collagen, and metalloproteinase (MMP)-3 and -9 were reduced after ATRvD1 administration. Post-septic mice treated with ATRvD1 were protected from the recruitment of IBA1+ cells. The interleukin-1β (IL-1β) levels were increased in the subAKI animal model, being attenuated by ATRvD1. Tumor necrosis factor-α (TNF-α), IL-10, and IL-4 mRNA expression were increased in the kidney of BSA-challenged post-septic mice, and it was also reduced after ATRvD1. These results suggest that ATRvD1 protects the kidney against a second insult such as BSA-induced tubulointerstitial injury and fibrosis by suppressing inflammatory and pro-fibrotic mediators in renal dysfunction after sepsis.